Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Mata Kuliah Asuhan Kebidanan Komunitas - Sumarni Sumarni; Hasbiah Wardani (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
The purpose of this research is to find out the effect of jigsaw cooperative learning model on the learning outcomes of community askeb courses at the D-III Midwifery Mkassar Stikes Midwifery Program in 2018. This type of research is an analytic survey with stady croos sectional approach to determine the effect of independent variables and variables dependent population in this research are all all second level students sampled from this research are some of the second level students in D-III Study Program Midwifery Mega Rezky Makassar with nonprobility sampling technique obtained 88 samples of this research done by distributing questionnaires from respondents. From the results of the study using the Chi-Square test obtained value = 0,000 smaller than the value of α = 0.05 thenρ <α which means that H0 is rejected and Ha is accepted. Conclusion There is an effect of jigsaw cooperative learning model on the learning outcomes of midwifery care courses in the D-III midwifery community.